Teorema Titik Tetap Kannan Pada Ruang Modular-2 - Nurnugroho, Burhanudin Arif (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2025)
Kannan's fixed point theorem, constructed initially on metric spaces, has been developed for several abstract spaces. This research will study Kannan's fixed point theorem on 2-modular spaces.